Penulisan Karya Seni Lagu Al-quran Di Malaysia Dan Indonesia - Mohd Zaini Zakaria; Mohd Yusuf Ismail; Muhammad Lukman Ibrahim; Sidek Ariffin (Usuli Faqih Research Centre, 2024)
Quranic art song is a knowledge that applies the method of singing tone, tempo and rhythm in reading the Quran. The development of this knowledge, particularly in Malay archipelago, was based on the central role of the qari and qariah and production of scientific papers in these disciplines which constitute civilizational heritage of Muslims. This article will focus on some books related to the art song of the Quran, especially in Malaysia and Indonesia based on the writing style of the books. This article applies qualitative method through analysis of documents to the works of Quranic art song in Malaysia and Indonesia. The results showed that the works of Quranic art song have helped lovers of the Quran to find out more about this knowledge.